Kemampuan Menulis Kalimat Menggunakan Kata Bantu Bilangan liàngcí (量词) Bahasa Mandarin Siswa Kelas XII SMA Insan Cendekia Syech Yusuf - Fitra Ramadhani; Ambo Dalle; Himala Praptami Adys (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
Fitra Ramadani,2021. " Student’s ability in Using Measure Words (liàngcí) in Mandarin  for Class XII High School Students Insan Cendekia Syech Yusuf ." Thesis. Makassar State University's Mandarin Language Education Study Program, Departement of Foreign Language Education, Faculty of Language and Literature. (supervised by Ambo Dalle and Himala Praptami Adys).This study is a quantitative descriptive study that aims to determine the ability of SMA Insan Cendekia Syech Yusuf XII grade students to write sentences using the measure word (liàngci) and the factors that influence it. The students in this study was 44 students of Insan Cendekia Syech Yusuf high school's class XII. The Student was chosen by using random sampling, and the sample in this study was  22 students in class XII MIA 1. The data of this research was obtained from a test of using measure words, while to find out the factors that influence the use of measure word, students used a questionnaire. The data were analyzed using the percentage technique. The results showed that the level of students' writing skills using measure word (liángci) was in the good category (80%). From the results of the questionnaire distribution, it was found that the factors that affect the students' ability to write sentences using measure word (liàngei) are: 1) Supporting factors are the methods used by the teacher in teaching Mandarin, the pleasure of students learning Mandarin. 2) The inhibiting factors are: Mandarin is a difficult subject; a lack of Mandarin textbooks; the students' little Mandarin vocabulary; parents rarely provide motivation to learn Mandarin. Keywords: Writing Ability, Measure Words (liangci), Mandarin Language.